Translational platelet research in patients with coronary artery disease: What are the major knowledge gaps? - Gurbel, Paul A.; Roe, Matthew T.; Jakubowski, Joseph A.; Shah, Svathi; Erlinge, David; Goodman, Shaun G.; Huber, Kurt; Chan, Mark Y.; Cornel, Jan H.; Tantry, Udaya S.; Ohman, E. Magnus (Thrombosis and Haemostasis, 2012)
Translational platelet function investigations performed in the percutaneous coronary intervention (PCI)-treated population receiving clopidogrel have identified high platelet reactivity to ADP (HPR) as a major risk factor for both acute as well as long-term ischaemic event occurrence, including stent thrombosis. Recent studies have highlighted the relation of single nucleotide polymorphisms of genes involved in clopidogrel absorption and metabolism to reduced pharmacokinetic and pharmacodynamic responses to clopidogrel. CYP 2C19 loss-of-function (LoF) allele carriage has been associated with increased thrombotic risk in the PCI population. However, there is no information regarding the utility of platelet function testing to predict outcomes in patients with stable coronary artery disease and in medically managed patients with acute coronary syndromes. Additionally, few studies have included longitudinal assessment of platelet function to assess a potential time-dependent relation to ischaemic event occurrence and no phase-III antiplatelet-therapy trial has included a large enough platelet function sub-study to examine the relation between on-treatment platelet reactivity, bleeding, and ischaemic event occurrence. Therefore, futher studies are needed to delineate the role of platelet function testing across the spectrum of symptomatic coronary artery disease.
Keywords: ADP receptors; clinical trials; antiplatelet drugs; platelet pharmacology; coronary syndrome